2019
DOI: 10.1148/radiol.2019190201
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vertebral Fractures by Convolutional Neural Networks to Predict Nonvertebral and Hip Fractures: A Registry-based Cohort Study of Dual X-ray Absorptiometry

Abstract: Background: Detection of vertebral fractures (VFs) aids in management of osteoporosis and targeting of fracture prevention therapies.Purpose: To determine whether convolutional neural networks (CNNs) can be trained to identify VFs at VF assessment (VFA) performed with dual-energy x-ray absorptiometry and if VFs identified by CNNs confer a similar prognosis compared with the expert reader reference standard. Materials and Methods: In this retrospective study, 12 742 routine clinical VFA images obtained from Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 19 publications
0
48
0
1
Order By: Relevance
“…Among the 32 studies that investigated fracture detection (Table 3), (66–97 ) 11 were on vertebral fractures, ( 66–76 ) 17 hip fractures, ( 74–90 ) and 10 other fracture sites such as humerus or wrist. ( 75,76,90–97 ) Nineteen studies developed CNN models for image analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 32 studies that investigated fracture detection (Table 3), (66–97 ) 11 were on vertebral fractures, ( 66–76 ) 17 hip fractures, ( 74–90 ) and 10 other fracture sites such as humerus or wrist. ( 75,76,90–97 ) Nineteen studies developed CNN models for image analysis.…”
Section: Resultsmentioning
confidence: 99%
“…( 69,70,73,75,86–89,92,96 ) Three studies shared their code for model development replication. ( 67,75,77 )…”
Section: Resultsmentioning
confidence: 99%
“…Substantial progress has already been made developing automated algorithms to accurately recognize vertebral fracture on lateral spine bone density images. ( 35 )…”
Section: Discussionmentioning
confidence: 99%
“…The use of Hologic Discovery, a later model, improved the sensitivity and specificity per vertebra to 83.6% and 99.1% respectively [71]. Computer-based deep learning methods have been developed for VFA, and a recent study including over 12,000 VFAs has reported an area under the receiver operating characteristic curve of 0.94 (95% confidence interval [CI]: 0.93, 0.95) for vertebral fracture detection [corresponding to a sensitivity of 87.4% (534 of 611) and specificity of 88.4% (2838 of 3211)] and performed comparably to the study radiologists (all who had more than 10 years of experience) [72].…”
Section: Dxa Vfa Methodsmentioning
confidence: 96%